Peningkatan Motivasi dan Prestasi Belajar Siswa pada Materi Virus dengan Pembelajaran Flipped Classroom berbantukan Media Audio Visual - Ni Luh Putu Suratna Dewi (IKIP PGRI Bojonegoro, 2020)
Abstract: This study aims to find out 1) the implementation of flipped classroom teaching by using audio-visual media, 2) the improvement of student’s motivation and learning achievement in class X MIPA 3, SMAN 1 Negara, Jembrana, Bali. This study is a Classroom Action Research using instruments in form of test questions, interview and observation guidelines. The data is collected using test, interview and observation methods. The data is validated using theory and data triangulations. The data analysis in this study uses the techniques of descriptive comparative and critical analysis. The indicators are measured by the improvement of student’s achievement above the Minimum Mastery Criteria, which is 70. The results of study show that 1) the implementation of flipped classroom teaching by using audio-visual media on the virus material has been integrated with a scientific approach, 2) the student’s motivation and learning achievement in class X MIPA 3 has increased. Increased motivation can be seen from the percentage of classical success of 1)student’s attention to pre-action activities by 37,71%, cycle I 56,57%, and cycle II 82,29%, 2) student’s activity in pre-action by 41,14%, cycle I 45,14%, and cycle II 71,43%, and 3) the student’s activeness in pre-action activities by 40,00%, cycle I 71,43%, and cycle II 81,71%, 4)the improvement of student’s learning achievement about the virus material can be seen from the percentage of classical success ranging from pre-action activities by 57,14%, cycle I 64,44%, and cycle II 76,51%. Keyword: motivation, learning achievement, virus, flipped classroom, audio visual. Abstrak: Tujuan penelitian ini adalah mengetahui 1) penerapkan pembelajaran flipped classroom berbantukan media audio visual, 2) peningkatan motivasi dan prestasi belajar siswa kelas X MIPA 3, SMAN 1 Negara, Jembrana, Bali. Penelitian ini merupakan Penelitian Tindakan Kelas dengan menggunakan instrumen berupa soal tes, pedoman wawancara, dan pedoman observasi. Data dikumpulkan dengan menggunakan metode tes, wawancara, dan observasi. Data divalidasi dengan triangulasi teori dan data. Analisis data pada penelitian ini menggunakan teknik deskripti komparatif dan teknik analisis kritis. Indikator keberhasilan diukur dengan adanya peningatakan prestasi belajar siswa di atas nilai Kriteria Ketuntasan Minimal (KKM), yaitu 70. Hasil penelitian menunjukkan bahwa 1) penerapkan pembelajaran flipped classroom berbantukan media audio visual pada materi virus sudah terintegrasi dengan pendekatan saintifik (5M). 2) motivasi dan prestasi belajar siswa kelas X MIPA 3, SMAN 1 Negara mengalami peningkatan. Peningkatan motivasi dapat dilihat dari persentasi keberhasilan klasikal dari, 1) perhatian siswa pada kegiatan pratindakan sebesar 37,71%, siklus I 56,57%, dan siklus II 82,29%, 2) keaktifan siswa pada kegiatan pratindakan sebesar 41,14%, siklus I 45,14%, dan siklus II 71,43%, dan 3) keaktifan siswa pada kegiatan pratindakan sebesar 40,00%, siklus I 71,43%, dan siklus II 81,71%. 2) peningkatan prestasi belajar siswa tentang materi virus dapat dilihat dari persentasi keberhasilan klasikal mulai dari kegiatan pratindakan sebesar 57,14%, siklus I 64,44%, dan siklus II 76,51%. Kata kunci: motivasi, prestasi belajar, virus, flipped classroom, audio visual.